Subject-specific computer simulation model for determining elbow loading in one-handed tennis backhand groundstrokes. - King, Mark A.; Glynn, Jonathan A.; Mitchell, Sean R. (Sports Biomechanics, 2011)
A subject-specific angle-driven computer model of a tennis player, combined with a forward dynamics, equipment-specific computer model of tennis ball–racket impacts, was developed to determine the effect of ball–racket impacts on loading at the elbow for one-handed backhand groundstrokes. Matching subject-specific computer simulations of a typical topspin/slice one-handed backhand groundstroke performed by an elite tennis player were done with root mean square differences between performance and matching simulations of < 0.5°over a 50 ms period starting from ball impact. Simulation results suggest that for similar ball–racket impact conditions, the difference in elbow loading for a topspin and slice one-handed backhand groundstroke is relatively small. In this study, the relatively small differences in elbow loading may be due to comparable angle–time histories at the wrist and elbow joints with the major kinematic differences occurring at the shoulder. Using a subject-specific angle-driven computer model combined with a forward dynamics, equipment-specific computer model of tennis ball–racket impacts allows peak internal loading, net impulse, and shock due to ball–racket impact to be calculated which would not otherwise be possible without impractical invasive techniques. This study provides a basis for further investigation of the factors that may increase elbow loading during tennis strokes.